Pengaruh Inklusi Keuangan, Literasi Keuangan, Inovasi dan Pengelolaan Keuangan Terahdap Kinerja UMKM di Yogyakarta - Ismalia, Dhiah Alda; Rinofah, Risal; Kusumawardhani, Ratih (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Micro, Small and Medium Enterprises (MSMEs) are to grow and develop businesses in order to build a national economy based on a just economic democracy. MSMEs in Indonesia have a significant contribution or role in expanding and absorbing new workers. MSMEs themselves have the advantage of producing consumer goods and services that are close to the needs of the community. There is still an obstacle that MSME actors still lack an understanding of the effects of inclusion, financial literacy, innovation and financial management in various types of businesses, especially on the performance of MSME by business actors. The reason of this consider is to decide the impact of budgetary incorporation, budgetary proficiency, advancement and monetary administration on the execution of MSMEs. The test measure utilized was 100 respondents who claim businesses. The examining method utilized in this ponder utilized a focused on inspecting procedure and the information were analyzed utilizing numerous relapse investigation to test the speculations. The comes about of this think about appear that the affect of monetary incorporation features a positive and significant affect on MSME execution, money related proficiency incorporates a negative and noteworthy affect on MSME execution, and development contains a positive affect on MSME execution. However, the impact is small, financial management has a positive impact on MSME performance, while financial management has a significant impact on MSME performance. It has a positive effect and has a significant impact on MSME performance.Â